Chemical characterization and antioxidant properties of fractions separated from extract of peanut skin derived from different industrial processes - Larrauri, Mariana (2016)
Peanut skins are a natural source of phenolic compounds with antioxidant activity and potential utility as food preservatives. The purpose of this study was to determine the chemical composition and antioxidant activities of extracts and purified fractions obtained from peanut skins prepared by blanching and roasting processes. Peanut skins from blanching and roasting processes were used to obtain crude extracts. These crude extracts were purified by solvent partition with n-hexane, ethyl acetate, and water. The ethyl acetate fraction obtained from blanched peanut skins was separated in a column packed with Sephadex LH-20 and separated into three new fractions of different colors: yellow, purple, and brown. The extraction yield, total phenols and flavonoids, scavenging activity towards different radicals (DPPH, hydroxyl, and superoxide anion), ferrous ion chelating activity, and accelerated sunflower oil oxidation were evaluated in crude extracts and purified fractions. The peanut skin fraction compounds were analyzed by HPLC-ESI-MS/MS. The extracts obtained from blanched peanut skins displayed a higher phenolic content (672.40 mg GAE/g) than those prepared from roasted peanut skins (416.92 mg GAE/g). Purification using solvent partition with ethyl acetate and column chromatography increased total phenolic content and antioxidant activity of peanut skin extracts. Fractions with higher total phenolic contents were associated with higher scavenging activities towards DPPH and superoxide anion radicals, and higher ferrous ion chelating activity. The yellow fraction exhibited higher flavonoid content and showed higher hydroxyl radical scavenging activity. In the accelerated sunflower oil oxidation test, peroxide values were lower in the color fraction samples. The main compounds present in peanut skin color fractions were phenolic acids, flavonoids, and stilbenes. The purified fractions of peanut skins displayed antioxidant properties and reduced peroxide formation in sunflower oil. These fractions could be used as a natural antioxidant in food products.